ANALYSIS ON DIFFERENT PHASES CYCLE IN PRODUCTION OF LAYING HENS - Hastuti Arifin (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2016)
This study aims to determine the productivity of the eggs produced in each phase of production of laying hens. The research was conducted in the village Bende Wundulako District of Kolaka that lasted approximately one month i.e. October to November 2011. The number of chickens is kept as many as 1,577 animals, strain CP 909. The productivity of egg laying hens is very different. Where in each cycle has increased from the initial production to experience the peak of production, which then slowly decreased. Daily egg production (hen-day production) at an early stage about 18.11%, 87.45% and the peak production of the final phase of 44.75%. While the percentage of egg production average weekly Phase I (17.45%), phase 2 (87.09%) and phase 3 (45.20%), for the production of eggs early (Hen-Housed Production EEG) the initial stage 18, 03%, peak production of 89.84% and 32.17% reject rate. Ties The result shows that the peak of egg production is high both in the production of eggs daily, weekly or early egg production Hen-Housed EEG) average is above 80%. So, it can be concluded that the productivity of egg laying hens are very different. Where in each cycle has increased from the initial production to experience the peak of production, on the cusp of production the number of eggs that produced very high